PARKING PULL IN THE TAMAN PASUK KAMELUH TOURISM AREA (STREET S. PARMAN, PALANGKA RAYA CITY) - jeki; Lola Cassiophea; Wiratno (Jurusan Pendidikan Teknologi Dan Kejuruan, 2021)
This type of research used in this research is descriptive research with a qualitative approach. The data needed to complete this research includes primary data obtained from field surveys which are used to obtain parking attraction and parking space capacity, while secondary data is obtained from the Perkim Service (Public Housing and Settlement Service) Palangka Raya City. The results of this study indicate that, Parking Space Capacity = 53 Ã· 0.75 = 70.6 motorbikes = 71 motorbikes, the highest parking accumulation is on Sunday at 15.00 WIB - 16.00 WIB for 62 motorbikes, the highest parking volume on Sunday is 258 vehicles/days/space, parking turnover rate (trun over) = 258 Ã· 145 = 1.7 vehicles/day/space, the average parking index per day is 10.71%, 11.41%, 6.1%, and park parking needs are 33 x 53 = 1,749 m2. Based on the results of the calculation of the parking attraction that occurs in the Taman Pasuk Kameluh area, Palangka Raya City, it is 258 vehicles/day/space. For travel attraction compared to the number of motorbike parking lots available to accommodate vehicles in the Kasuk Kameluh park area, it is 70.6 vehicles/day. So based on the results obtained, the demand for parking space exceeds the existing parking capacity, only 53 parking pedals (demand) exceed the existing parking capacity.